2010
DOI: 10.4088/jcp.09m05258gre
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Second-Generation Antipsychotics and Perphenazine on Depressive Symptoms in a Randomized Trial of Treatment for Chronic Schizophrenia

Abstract: Background According to the American Psychiatric Association Clinical Practice Guidelines for schizophrenia, second-generation antipsychotics may be specifically indicated for the treatment of depression in schizophrenia. We examined the impact of these medications on symptoms of depression using the data from the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE), conducted between January 2001 and December 2004. Method Patients with DSM-IV–defined schizophrenia (N = 1,460) were assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 41 publications
(39 reference statements)
1
18
1
Order By: Relevance
“…CDSS for depression). Furthermore, this study adopted CDSS score of ≥ 6 as a criterion indicative of MDE consistent with previous work examining the effect of antipsychotics on depressive symptoms in the CATIE sample (Addington et al, 2010). However, since this criterion did not include the number and duration of depressive symptoms, it does not necessarily align with MDE criteria as outlined in the DSM-5 (American Psychiatric Association, 2013).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…CDSS for depression). Furthermore, this study adopted CDSS score of ≥ 6 as a criterion indicative of MDE consistent with previous work examining the effect of antipsychotics on depressive symptoms in the CATIE sample (Addington et al, 2010). However, since this criterion did not include the number and duration of depressive symptoms, it does not necessarily align with MDE criteria as outlined in the DSM-5 (American Psychiatric Association, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…Exploratory analyses suggested that risperidone may be more effective than olanzapine in improving depressive symptoms in chronic schizophrenia with MDE. However, two randomized, double-blind, RCTs comparing olanzapine and risperidone in chronic schizophrenia with concomitant MDE (Addington et al, 2010) and post-psychotic depression (Dollfus et al, 2005), respectively, reported no differences in antidepressant effects between these agents. The small sample size associated with our exploratory findings suggests caution in any interpretation of these results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some clinical trials found that quetiapine reduced depressive symptoms considerably in schizophrenic patients [25] and bipolar depression [26,27]. Although some experts view that its antidepressant effect may not be superior to other antidepressants [28], this is the only agent approved for the treatment of acute bipolar depression [29].…”
Section: Introductionmentioning
confidence: 99%